6a+4b-a+9b=

Simple and best practice solution for 6a+4b-a+9b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+4b-a+9b= equation:


Simplifying
6a + 4b + -1a + 9b = 0

Reorder the terms:
6a + -1a + 4b + 9b = 0

Combine like terms: 6a + -1a = 5a
5a + 4b + 9b = 0

Combine like terms: 4b + 9b = 13b
5a + 13b = 0

Solving
5a + 13b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-13b' to each side of the equation.
5a + 13b + -13b = 0 + -13b

Combine like terms: 13b + -13b = 0
5a + 0 = 0 + -13b
5a = 0 + -13b
Remove the zero:
5a = -13b

Divide each side by '5'.
a = -2.6b

Simplifying
a = -2.6b

See similar equations:

| 7(4x+9)=165 | | -1=28x+21 | | 7a-4=10-2a-41 | | -4v^2+28v+32=0 | | 12-x/8=-1 | | 3a-a+5-6= | | 4+49x=21x+16 | | 5(6x-4)=190 | | 4.2x=-24x-48 | | (9-u)(2u-1)=0 | | 4+49=21x+16 | | 5x^2+56x+27=0 | | X/3-5=5 | | 30b=5c | | 5(82.5)+3y=586.5 | | 3(12x+25)=205 | | 3x+32=15x+8 | | 3x+32=15x | | z^-4/3x^7 | | 5d-2d=6+3d | | x/3-4/x=4/3 | | x^3+12x-4=0 | | 18xy= | | 6y+13=11+5Y | | 3/8=n/16 | | 3(p+2)=3(2p-4)+4 | | 6m-4=-5(m+3) | | 26+x(17)=-42 | | 3(4x+7)=6x+75 | | 0.25x+90=1.25x | | Y=5x^4+2x^2 | | 4t+3=2t+8 |

Equations solver categories